(untitled) - Shilling, Dana (New York, 2002)
This is an extremely well-conceived, clearly written, and authoritative presentation of several related intellectual property disciplines. It will be valuable both to business executives and nonspecialized lawyers. Serious readers should get up to speed rapidly because Ms. Shilling focuses on the real issues in an effective, user-friendly manner
Keywords: Trademarks,Competition, unfair; Law and legislation; United States,United States